The Relationship between knee joint angle, stretch-shorten cycle performance, and jump distance in ski jumping - Paradis, S.; McBride, J.; Foster, C.; Kirnozeck, T.; Lephart, S.; Fu, F. (2001)
The purpose of the take-off is: (1) to give the jumper-ski system a maximum velocity, (2) to produce a favorable body position at the jump's edge, and (3) to provide an initial turning moment for the forward rotation of the body over the skis immediately after take-off (Campbell, 1980). This experiment adds another purpose to the take-off: to perform a stretch-shorten cycle. The data show the existence of a stretch-shorten cycle (SSC) movement 0.08 s before the edge of the ski jump lasting approximately 66 ms. An elite ski jumper must utilize the SSC movement to increase their jump distance. It is important to recall the information in Figure 2. The data demonstrate there were a significant (á= .05) quadratic relation between flexion of the knee joint and the jump distance. This demonstrates a relationship between optimal knee joint flexion and maximum jump distance. This suggests that when a jumper resists against and doesn.t utilize the centrifugal force entering the take-off table to flex the knee joint, they may not be harnessing the full potential of the stretch-shorten cycle movement. Also, the jump distance may be hindered if the athlete flexes the knees too much. It is possible the proper knee joint flexion angle may create a build-up of elastic energy resulting in a more explosive knee extension velocity. This is all dependent on the jumper's ability to produce a quality take-off motion followed by a stable flight phase. Therefore, the stretch-shorten cycle may be an important factor in determining the length of the jump. It is important to remember that several aspects must work together to produce a long jump distance. Not only does the SSC movement exist, but there also may be an ideal amount of knee flexion to utilize the elastic energy in the SSC movement to produce a successful jump distance. This study concluded that when an elite jumper utilized a proper stretch-shorten movement, in combination with proper form on the take-off table and in the air, they would produce a longer jump distance.